Ultra-Low-Dose Whole-Body Computed Tomography Protocol Optimization for Patients With Plasma Cell Disorders: Diagnostic Accuracy and Effective Dose Analysis From a Reference Center - Tore, Davide; Rampado, Osvaldo; Guarnaccia, Carla; Mina, Roberto; Oronzio, Maria; Santonocito, Ambra; Serafini, Alessandro; Strazzarino, Giulio Antonino; Gianusso, Laura; Bringhen, Sara; Fonio, Paolo; Depaoli, Alessandro (Frontiers in Oncology, 2021)
Background: the whole-body low dose CT (WBLDCT) is the first-choice imaging technique in patients with suspected plasma cell disorder to assess the presence of osteolytic lesions. We investigated the performances of an optimized protocol, evaluating diagnostic accuracy and effective patient dose reduction using a latest generation scanner. Methods and Materials: Retrospective study on 212 patients with plasma cell disorders performed on a 256-row CT scanner. First WBLDCT examinations were performed using a reference protocol with acquisition parameters obtained from literature. A phantom study was performed for protocol optimization for subsequent exams to minimize dose while maintaining optimal diagnostic accuracy. Images were analyzed by three readers to evaluate image quality and to detect lesions. Effective doses (E) were evaluated for each patient considering the patient dimensions and the tube current modulation. Results: A similar, very good image quality was observed for both protocols by all readers with a good agreement at repeated measures ANOVA test (p>0.05). An excellent inter-rater agreement for lesion detection was achieved obtaining high values of Fleiss’ kappa for all the districts considered (p<0.001). The optimized protocol resulted in a 56% reduction of median DLP (151 mGycm, IQR 128-188 mGycm vs 345 mGycm, IQR 302-408 mGycm), of 60% of CTDIvol, (2.2 mGy, IQR 1.9-2.7 mGy vs 0.9 mGy, IQR 0.8-1.2 mGy). The median E value was about 2.6 mSv (IQR 1.7-3.5 mSv) for standard protocol and about 1.5 mSv (IQR 1.4 - 1.7 mSv) for the optimized one. Dose reduction was statistically significant with p<0.001. Conclusions: protocol optimization makes ultra low dose WBLDCT feasible on latest generation CT scanners for patients with plasma cell disorders with effective doses inferior to conventional skeletal survey while maintaining excellent image quality and diagnostic accuracy. Dose reduction is crucial in such patients as they are likely to undergo multiple whole-body CT scans during follow-up.